Kreativitas Model Cetakan dan Packaging Saka Untuk Meningkatkan Nilai Tambah Industri Rumahan Pasca Bencana Galodo - Merry Thressia; Dian Wahyoni DF; Mulyadi Mulyadi (PELANTAR PRESS, 2024)
The existence of a home industry is very important for local communities, because it provides benefits for individuals/groups that run it, one of the best Saka-producing villages is in NagariBukik Batabuah. The galodo disaster that befell this village had a major impact on people's livelihoods, in the midst of this downturn the village head, together with residents immediately adapted to find other alternatives, namely developing a model of Saka moulds and packaging that usually uses convex coconut shells, so that consumers are reluctant to buy them. From this problem it is concluded: a). loss of community livelihood, b). people who used to farm switched to cultivating land, c). industry players do not have knowledge in the field of mould and packaging models, d). low knowledge of industry players about marketing through (TTG). The purpose of the activity is to provide counseling, workshops to industry players to increase creativity and innovation in processing Saka mould and packaging models, so as to increase community income, carried out 3 days with lecture methods, brainstorming, workshops, with 40 participants: 1). Saka industry players realise the importance of creative and innovative business development on Saka mould models made from silicone because the models are diverse and in demand by consumers, heat resistant, durable for the long term, 2). improve the shape of packaging to be more attractive, 3). Saka industry players actively follow the development of TTG to market production to a wider area